First description of the male and subgravid female of Philometra serranellicabrillae Janiszewska, 1949 (Nematoda: Philometridae), a gonad-infecting parasite of the comber Serranus cabrilla (Linnaeus) (Serranidae) off Tunisia - Ghanmi, Nessrine; González-Solís, David; Gargouri, Lamia (Systematic parasitology, 2019)
The male and subgravid female of Philometra serranellicabrillae Janiszewska, 1949 (Philometridae) collected from the gonads of Serranus cabrilla (Linnaeus) (Serranidae) off Tunisia are described for the first time based on light and scanning electron microscopical studies. The male of this nematode can be separated from other congeneric gonad-infecting nominal species in the structure and shape of the gubernaculum (e.g. absence of a dorsal protuberance and a median smooth field). The shape of the male posterior region is unique in that it bears a pair of big circular papillae posterior to the cloacal opening, which is also present in other Philometra spp. from serranids, i.e. P. indica Moravec & Manoharan, 2014, P. inexpectata Moravec, Chaabane, Justine & Neifar, 2016 and P. jordanoi (López-Neyra, 1951) Yamaguti, 1961. Moreover, P. serranellicabrillae differs from its congeners in other fish families from the Mediterranean Sea, in the length of spicules and gubernaculum.
Keywords: Dracunculoidea; druhová specificita; Male; Fish Diseases; Gonads; mužské pohlaví; Species Specificity; Tunisko; Animals; Percoidea; ženské pohlaví; Microscopy, Electron, Scanning; zvířata; nemoci ryb; Bass; Tunisia; Female; mikroskopie elektronová rastrovací; gonády